BAYANGAN AKAN BANGSA DALAM KONTEKS HAK UNTUK MENENTUKAN NASIB SENDIRI: SUATU WACANA - Moeliono, Tristam Pascal (Penerbit Universitas Atma Jaya Yogyakarta, 2020)
Two issues shall be discussed: what is meant by people’s right to self determination and how has it been realized, also in the context of indigenous-tribal peoples. Analysis shall be done, by using a juridical doctrinal method. The purpose would go beyond explaining but also induce understanding of people’s right to self determination in the context of nation states. One determining faktor in the construction of a nation state is the emergence of an imagined solidarity between peoples from different races, tribes, or religious beliefs, being the result of suffering under colonialism. Notwithstanding that indigenous or tribal peoples may and in fact experience similar suffering under the state they are considered to be part of, international law, while recognizing their right to self determination, does not fully extend the same scope of rights to them.